Study and Design of a Multi-range Programmable Sensor for Temperature Measurement - Alsnaie, K.; Ghaly, S. M. A.; Ali, M. A. (Engineering, Technology & Applied Science Research, 2022)
In this paper, a wide-range high-precision sensor has been designed in order to accurately measure the temperature in a medium with arbitrary temperature variation and the implementation of a wide-spectrum temperature measurement system with a self-selected multi-sensor has been realized. This multi-sensor core is made up of different sensors combined to measure different temperature ranges. This concept can be used for high-precision temperature measurement in electrical capacitance tomography applications. The proposed technique is well suited for temperatures in boilers, industries, and everywhere high temperature measurement sensitivity is needed by using different combined temperature sensors of high precision.